UNVEILING THE MEANING AND PRACTICE OF HUMAN RESOURCE MANAGEMENT STRATEGIES IN IMPROVING MSME PERFORMANCE - Muh. Husriadi (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2026)
This research is based on the fact that human resource management in MSMEs is still largely carried out informally and is heavily influenced by personal relationships between business owners and employees. This situation often makes the relationship between HR practices and business performance unclear and difficult to measure systematically. Although HR is understood as a vital intangible asset that plays a role in creating business excellence, there are still limitations in understanding how these practices are truly interpreted and implemented in the context of MSMEs in areas such as Kendari City. This study aims to explore the meaning and practice of HR management in MSMEs, while also examining how this relates to business performance. The approach used is a qualitative phenomenological approach with data collection techniques through in-depth interviews, field observations, and thematic analysis with 12-15 informants consisting of MSME owners and key employees in the food and beverage sector in Kendari City. The results show that HR management is better understood as a process of building warm relationships and maintaining emotional closeness, often referred to as "heart management." Emerging practices include proximity-based recruitment, informal rewards that emphasize loyalty, and flexible and less structured performance evaluations that still foster a friendly work environment. Therefore, this research emphasizes the importance of developing HR strategies that remain relevant to local culture while simultaneously moving toward a more measurable system that allows for continuous monitoring and improvement of business performance without diminishing existing family values.